The War on Terror and the Fiction of Agency: A Critical Analysis of Mohsin Hamid’s The Reluctant Fundamentalist (2007) - Ilyas, Muhammad; Shah, Irfan Ali (Pakistan Languages and Humanities Review, 2025)
The present study examines how Mohsin Hamid foregrounds the agency of Pakistanis and Pakistani writers in challenging and reshaping the dominant Western discourse. During the war on terror, Pakistan and the United States maintain an ambivalent relationship. Pakistan, supposedly a key ally, was always accused of pursuing conflicting interests and double gamer. Consequently, the Pakistani narrative was not heard in the West and the Pakistani agency often ignored or unnoticed. The present study employs Ambreen Hai’s (2009) three-dimensional model of human agency for textual analysis of Mohsin Hamid’s The Reluctant Fundamentalist (2007). The model is based on three-sided nature of agency as argued by Hai in her book, Making Words Matter: The Agency of Colonial and Postcolonial Literature. The paper concludes that although Changez as an agent of change tries to reclaim agency, however, his agency is used by the dominant western discourse against him. In addition, the protagonist of the novel remains a non-agent at the end of the novel the way he had been denied agency by American discourse in the beginning of the novel. The researcher recommends that other novels or literary texts may also be explored to understand how other writers tackle the issue of Agency in the wake of post 9/11 socio- cultural and Geopolitical scenarios